Evidence Based Health Informatics: 10 Years of Efforts to Promote the Principle - Rigby, M.; Ammenwerth, E.; Beuscart-Zephir, M.-C.; Brender, J.; Hyppönen, H.; Melia, S.; Nykänen, P.; Talmon, J.; de Keizer, N. (Yearbook of Medical Informatics, 2013)
Objectives: To present the importance of Evidence-based Health Informatics (EBHI) and the ethical imperative of this approach; to highlight the work of the IMIA Working Group on Technology Assessment and Quality Improvement and the EFMI Working Group on Assessment of Health Information Systems; and to introduce the further important evaluation and evidence aspects being addressed.Methods: Reviews of IMIA, EFMA and other initiatives, together with literature reviews on evaluation methods and on published systematic reviews.Results: Presentation of the rationale for the health informatics domain to adopt a scientific approach by assessing impact, avoiding harm, and empirically demonstrating benefit and best use; reporting of the origins and rationale of the IMIA- and EQUATOR-endorsed Statement on Reporting of Evaluation Studies in Health Informatics (STARE-HI) and of the IMIA WG's Guideline for Good Evaluation Practice in Health Informatics (GEP-HI); presentation of other initiatives for objective evaluation; and outlining of further work in hand on usability and indicators; together with the case for development of relevant evaluation methods in newer applications such as telemedicine. The focus is on scientific evaluation as a reliable source of evidence, and on structured presentation of results to enable easy retrieval of evidence.Conclusions: EBHI is feasible, necessary for efficiency and safety, and ethically essential. Given the significant impact of health informatics on health systems, care delivery and personal health, it is vital that cultures change to insist on evidence-based policies and investment, and that emergent global moves for this are supported.
Keywords: Evidence-based health informatics; evaluation; evidence; health informatics; ethics